Effects of plasma-activated water on germination ‎and initial seedling growth of wheat - Ahad Asghari; Elnaz Sabbaghtazeh; Nasrin Roshan Milani; Mohammad Kouhi; Alireza Ahangarzadeh Maralani; Parvin Gharbani; Alireza Sotoudeh Khiaban (PLoS ONE, 2025)
In this research, the effect of seed halopriming with plasma activated water (PAW) on wheat germination parameters have been studied. Response surface methodology was used to investigate the effect of three factors including: 1) type of water (distilled water, 0.2 and 0.4 min/mL PAW), 2) priming time (1, 3 and 5 h), and 3) salinity of the priming solution (0, 25 and 50 mmol/L NaCl) on wheat germination parameters. The results revealed that increasing PAW levels up to 0.18 min/mL led to an increase in seed germination percentage, seedling weight (both fresh and dry), seedling length, vigor indexes A and B, and water uptake and decreasing mean germination time. Increasing the level of PAW by more than 0.18 min/mL had a negative effect on these parameters. The fresh and dry weight of the seedlings respectively at the 0.18 and 0.2 min/mL levels of PAW, in all salinity levels, had the highest value. The effect of halopriming on enhancing seedling length was more than other characteristics. The optimum ranges of PAW, salinity and priming time were 0.13 min/mL, 10.3 mmol/L and 120.22 min for germination percentage, 0.18 min/mL, 15 mmol/L and 191.24 min for seedling fresh weight, 0.15 min/mL, 13.84 mmol/L and 221.2 min for seedling dry weight, 0.33 min/mL, 24.36 mmol/L and 152.62 min for mean germination time, 0.11 min/mL, 19.03 mmol/L and 177.77 min for vigor indexes A and 0.1 min/mL, 18.1 mmol/L and 178.99 min for vigor indexes B.